PENGARUH PERSEPSI ORANG TUA TERHADAP PROGRAM MAKAN BERGIZI GRATIS DI LEMBAGA PAUD - Amelia Putri, Sifah; Yossi Srianita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the effect of parental perception on the Free Nutritious Meal Program (MBG) in an early childhood education institution. The research was motivated by the importance of parental acceptance and involvement in supporting school-based nutrition programs for young children. A quantitative correlational design was used. The research was conducted at RA Amanah Nashrul Ulum, Bekasi, with 50 parents of students as respondents. Data were collected using a Likert-scale questionnaire covering parental perception and the implementation of the MBG program. The data were analyzed through validity testing, reliability testing, classical assumption testing, simple linear regression, partial t-test, and coefficient of determination using SPSS. The findings show that parental perception of the MBG program is in the moderate category, with an average score of 42.38 out of an ideal maximum score of 60. The regression analysis indicates a positive and significant effect of parental perception on the MBG program, with tcount = 19.101 and Sig. = 0.000. The coefficient of determination shows that parental perception explains 88.4% of the variation in the MBG program. These findings indicate that parental knowledge, trust, school-parent communication, and program implementation quality are important factors in supporting the success of the MBG program in PAUD.